The importance of Hair and Scalp Hygiene for pediculus humanus capitis epidemic prevention - Maria Vonny Rumampuk (Universitas Airlangga, 2017)
Introduction: Pediculus humanus capitis have cosmopolite attributes, and normally affect school age children. This research aims at obtaining the number of people infested with pediculus humanus capitis and is categorized by the age, sex, education, social-economic status, way of life, and prevalence of lice, louse nymphs and eggs among children living in ten orphanages within the Province of North Sulawesi in 2012. Method: The research is designed using crosssectional approach and is based on samples taken from 568 respondents. Result: The fi ndings of this research indicate that 106 (18.66%) children are infested by Pediculus humanus capitis. Statistic test using chi-square approach results in a score of p<0.05 which indicates a correlation between hair length, type of cleansing agents used for hair wash, the frequency of hair wash, the use of towels, the use of combs, sleeping habit, scalp itchiness, and scalp irritation with lice prevalence in the hair. Multivariate analysis using logistic regression test results in a score of p<0.05 attributable to the prevalence of adult lice among children with long hair, hairwash frequency, use of comb and sleeping habit. Those that are mostly attributable to lice prevalence is hairwash frequency with a score of Wald 58 and OR 326. Discussion: Pediculus humanus capitis is found among children of 7 - 12 years, and dominated by girls, elementary school education, low social-economic status, unhealthy way of life, comprising children living in densely populated orphanages. Children infested with head lice suffer from head itches and irritation. It is recommended that orphanages make efforts of head lice prevention, control and eradication as well as instilling the awareness in governesses and orphans of the importance of scalp and hair hygiene. Keywords: epidemiology, Pediculus humanus capitis, child/children, orphanage/orphanages.